Sosialisasi Penggunaan Media Papan Perkalian Bagi Orang Tua untuk Meningkatkan Kemampuan Berhitung Anak Sekolah Dasar di Rumah - Patri Janson Silaban; Afri Indah Yohana Sitohang; Aldorino Aldorino; Devany Silalahi; Lasma Situmeang; Viktor Simamora (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Numeracy skills are one of the basic competencies that must be mastered by elementary school students because they are the basis for learning various mathematical concepts. However, there are still many students who have difficulty understanding the concept of multiplication so that they need optimal assistance, both at school and at home. One of the obstacles faced is the limited use of interesting learning media and the lack of understanding of parents in accompanying children to learn. Therefore, this community service activity aims to provide socialization to parents about the use of multiplication board media as a means of assisting children learning at home. The method of implementing activities includes the preparation stage, the implementation of socialization, demonstrations of the use of media, the practice of media use by parents and children, as well as evaluation through observation, questionnaires, and short interviews. The results of the activity showed that parents were able to understand how to use multiplication board media and were more confident in accompanying their children to study at home. The use of multiplication board media is also able to increase children's interest and enthusiasm in learning multiplication so that the learning process becomes more fun. Thus, this socialization activity provides benefits for parents in supporting the children's learning process and helping to improve the numeracy skills of elementary school students.